Blood Profile of Vitamin A and β-Carotene During Post-Partum Period in Surti Goats - Manat, Tanvi D.; Chaudhary, Sandhya S.; Singh , Virendra Kumar; Patel , Sanjay B. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was undertaken to study levels of vitamin A and β-carotene in blood of post partum Surti goats. 40 Surti goats were selected comprising of 20 goats with recent parturition (treatment group) and 20 non-pregnant animals (control group). Blood collection was done on 0, 7, 14, 21, 30 and 45 day post-kidding (treatment group) and once from control group and analyzed for Vitamin A and β-carotene. Both the analytes were significantly low on 0 day. Significant difference (P
Keywords: Postpartum period; Surti goat; vitamin A; β-carotene